Crystal structure, spectroscopic, DNA binding studies and DFT calculations of a Zn(ii) complex. (19th March 2019) - Mondal, Satyajit; Chakraborty, Moumita; Mondal, Antu; Pakhira, Bholanath; Mukhopadhyay, Subhra Kanti; Banik, Avishek; Sengupta, Swaraj; Chattopadhyay, Shyamal Kumar
Abstract : A highly fluorescent Zn(ii ) complex and its DNA-binding and bio-imaging applications are reported. Abstract : Herein we report, a mononuclear, highly fluorescent zinc(ii ) complex Zn(L)(N3 )(H2 O) (1 ) that was prepared by an easy "one pot" method, in which the tridentate Schiff base ligand ( E )-4-((2-(dimethylamino)ethylimino)methyl)-5-(hydroxymethyl)-2-methylpyridin-3-ol (HL) was generated in situ . The compound is characterized by various spectroscopic techniques, and its structure was determined by single crystal X-ray diffraction studies. DFT calculations were used to understand the electronic structures of the ligand and the complex, and TD-DFT calculations were performed to interpret the nature of the electronic transitions observed in their UV-vis spectra. In the complex, Zn(ii ) is found to be penta-coordinated with one azide ligand, an aqua ligand and a monoanionic tridentate N, N, O-donor ligand. In an aqueous methanol (1 : 9 by volume) solution, at the physiological pH (0.01 M Tris–HCl buffer, pH 7.4), compound1 exhibits an intense greenish blue fluorescence ( λ ex 390 nm, λ em 462 nm), whose intensity is about 17-fold stronger than that of the free ligand. Compound1 is found to show significant DNA binding activity. The pyridoxal appended tridentate ligand can be used for the bio-imaging of Zn(ii ).